2019
DOI: 10.1002/pbc.27948
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of pretransplant chemotherapy in the treatment of juvenile myelomonocytic leukemia

Abstract: Background: Despite the intensity of hematopoietic stem cell transplantation (HCT), relapse remains the most common cause of death in juvenile myelomonocytic leukemia (JMML). In contrast to other leukemias where therapy is used to reduce leukemic burden prior to transplant, many patients with JMML proceed directly to HCT with active disease. The objective of this study was to elucidate whether pre-HCT therapy has an effect on the molecular burden of disease and how this affects outcome post-HCT.Procedure: Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…In conclusion, although the long-term advantage of azacitidine therapy remains to be fully assessed, this prospective clinical trial has shown that azacitidine therapy prior to HSCT is a safe and efficacious option for patients with JMML. Whether response to upfront therapy like azacitidine or combination chemotherapy 24 is simply a biomarker for favorable disease or can effectively reduce post-HSCT JMML recurrence will have to be addressed in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, although the long-term advantage of azacitidine therapy remains to be fully assessed, this prospective clinical trial has shown that azacitidine therapy prior to HSCT is a safe and efficacious option for patients with JMML. Whether response to upfront therapy like azacitidine or combination chemotherapy 24 is simply a biomarker for favorable disease or can effectively reduce post-HSCT JMML recurrence will have to be addressed in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA samples were sequenced using a custom amplicon-based sequencing approach (Paragon Genomics, Hayward, CA, USA) targeting 26 genes that are known to be recurrently mutated in JMML 18 (Supplementary Table 1 and Supplementary methods). A VAF of 0.05 (=5%) at diagnosis was required for reporting.…”
Section: Next-generation Sequencing Of Jmml-associated Mutationsmentioning
confidence: 99%
“…With knowledge of the NUP98-NSD1 fusion, chemotherapy would have been continued until RT-PCR was negative, as achieving a molecular remission before transplant has been associated with improved outcomes in both JMML and AML. 19,20 In addition, it would have prompted use of a less intensive myeloablative conditioning regimen, which may have spared some of the patient's post-HCT toxicities. Lastly, this finding was of benefit by offering the ability to track the patient's disease status more accurately post-HCT using RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal ultrasound was negative for hepatosplenomegaly. Cytogenetic analysis showed a single abnormal cell with a 44,X,-X,del(9)(q13q22),-16 [1],46,XX [20] karyotype. FLT3-ITD, CEBPA, and NPM1 were tested using next generation sequencing and were all normal.…”
Section: Case Reportmentioning
confidence: 99%